ANALISIS PENGELOLAAN KEUANGAN MAHASISWA PERANTAUAN MBKM ASISTENSI MENGAJAR DI FKIP UNIVERSITAS TANJUNGPURA - Izzati Ramadhannisa; Junaidi H. Matsum; Warneri Warneri (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This research was conducted on Teaching Assistance MBKM Students of FKIP Tanjungpura University, who got a MBKM place at Pontianak Cooperative High School. This research aims to find out how financial management among overseas students, and how their knowledge about how to manage finances. The research approach is qualitative research with a case study type of research. The source of research data is MBKM overseas students who PLP at SMA Koperasi. Data collection was carried out by distributing interview questionnaires to overseas students. The MBKM Teaching Assistance program lasts about four months, from August to November 2022. Those who take part in this Teaching Assistance also receive operational money which is given once a month. The results of the study show that, of the nine overseas students, there are two students who are not aware of the importance of setting aside their finances properly. There are two students who already understand that they cannot only rely on sources of income from parents, so they do odd jobs. And there are two people who admit that every month, they experience more money shortages at the end of the month, even though both are aware of setting aside their savings, and one of the two people does a part-time job.